Illusion Thermotics. Issue 22 (17th April 2018) - Hu, Run; Zhou, Shuling; Li, Ying; Lei, Dang‐Yuan; Luo, Xiaobing; Qiu, Cheng‐Wei
Abstract: "Fata Morgana" or "Mirage" phenomena have long been captivated as optical illusions, which actually relies on gradient‐density air or vapor. Man‐made optical illusions have witnessed significant progress by resorting to artificially structured metamaterials. Nevertheless, two long‐standing challenges remain formidable: first, exotic parameters (negative or less than unity) become inevitable; second, the signature of original object is altered to that of a virtual counterpart. It is thus not able to address the holy grail of illusion per se, since a single virtual object still exposes the location. In this study, those problems are successfully addressed in a particular setup—illusion thermotics, which identically mimics the exterior thermal behavior of an equivalent reference and splits the interior original heat source into many virtual signatures. A general paradigm to design thermal illusion metadevices is proposed to manipulate thermal conduction, and empower robust simultaneous functions of moving, shaping, rotating, and splitting heat sources of arbitrary cross sections. The temperature profile inside the thermal metadevice can mislead the awareness of the real location, shape, size, and number of the actual heat sources. The present concept may trigger unprecedented development in other physical fields to realize multiple functionalized illusions in optics, electromagnetics, etc. Abstract : Existing optical/thermal illusions fail to address the holy grail of illusion per se, since a single virtual object still exposes the location. A solution to this problem is found in illusion thermotics, which identically mimics the exterior thermal behavior of an equivalent reference and splits the interior original heat source into many virtual signatures to enhance the deceptiveness unprecedentedly.